Assessment of knowledge, attitude and practice on people with diabetes mellitus in general medicine department of tertiary care teaching hospital - Neupane, Dinesh Raj; N., Upendra; Thomas, Jaiji; Joy, Jojymol K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes has become a scourge to mankind. According to World Health Organization, over 366 million people are affected with diabetes worldwide and its number is likely to be doubled by 2030. The study was conducted to educate the patients regarding diabetes which may lead in improving the quality of life of the patients. However, prior to educating and intervening the patients regarding the disease, KAP study was conducted to assess the current status and behaviour of the patients towards Diabetes Mellitus (DM). Methods: The study was cross sectional study conducted for the period of six months starting from July 2019 to December 2019 in medicine department of Tertiary care teaching Hospital, Karnataka. Pre-structured questionnaires were formed for data collection. Results: In our current study, 60 (46.15%) were men and 70 (53.85%) women. Out of the total of ten knowledge question asked, average of men answering correctly were 29.5% and women answered correctly were 21% and rest were incorrect. Among the total of five attitude questions asked, average of 25.08% men agreed to correct response and 18% women agreed to correct response rest disagreed whereas in total of six practice questions average of 26.92% men and 14.61% women claimed that they practice the activities as per the questionnaires. Conclusions: Knowledge of diabetic patients was fairly good, attitude and practices were not satisfactory females showed relatively poor response towards the disease in comparison to male. We strongly feel that there is a need to design and develop individualized diabetes educational program to aware and educate people about diabetes.